2005
DOI: 10.1152/ajpregu.00846.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil positively regulates plasma leptin and adiponectin levels in sucrose-fed, insulin-resistant rats

Abstract: Insulin resistance and adiposity induced by a long-term sucrose-rich diet (SRD) in rats could be reversed by fish oil (FO). Regulation of plasma leptin and adiponectin levels, as well as their gene expression, by FO might be implicated in these findings. This study was designed to evaluate the long-term regulation of leptin and adiponectin by dietary FO in a dietary model of insulin resistance induced by long-term SRD in rats and to determine their impact on adiposity and insulin sensitivity. Rats were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
154
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(178 citation statements)
references
References 51 publications
16
154
0
8
Order By: Relevance
“…Our data suggest that fish oil feeding resulted in a decrease of WAT and body weight and improved insulin sensitivity in female KK mice. Rossi et al reported that shifting the source of fat to fish oil for 2 months increased plasma levels of both leptin and adiponectin in rats 25) . Haluzik et al reported that fenofibrate treatment did not increase serum adiponectin in mice fed a carbohydrate diet 26) .…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that fish oil feeding resulted in a decrease of WAT and body weight and improved insulin sensitivity in female KK mice. Rossi et al reported that shifting the source of fat to fish oil for 2 months increased plasma levels of both leptin and adiponectin in rats 25) . Haluzik et al reported that fenofibrate treatment did not increase serum adiponectin in mice fed a carbohydrate diet 26) .…”
Section: Discussionmentioning
confidence: 99%
“…These increases in adiponectin may subsequently upregulate genes involved in fatty acid oxidation (Yamauchi et al, 2002;Rossi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Leptin concentration, on the other hand, was inversely associated with membrane eicosapentaenoic and docosahexaenoic acids. Recently, leptin-lowering effect of long-chain omega-3 fatty acids (fish oil) has been demonstrated in dietinduced rodent model of obesity (Rossi et al, 2005;Selenscig et al, 2010). Plasma leptin concentration is closely linked with fat mass and fat mass itself can be modulated by longchain omega-3 fatty acids as we have previously observed (Aurora et al, 2005).…”
Section: Discussionmentioning
confidence: 55%